A42 UNDERUSE OF IRON THERAPY UPON DISCHARGE FOR ANEMIC PATIENTS WITH ACUTE GASTROINTESTINAL BLEEDING. (1st March 2018) - Fortinsky, K J; Bernick, J; Agarwal, A; Bernstein, M; Lin, Y; Gallinger, Z; Ye, P; Barkun, A N; Weizman, A V
Abstract: Background: Many patients with gastrointestinal bleeding (GIB) are discharged from hospital with anemia. One recent study found that iron therapy leads to more rapid correction of anemia in patients after GIB. Current guidelines do not address the utility of iron in these patients and recent survey data suggests that clinicians do not routinely prescribe iron therapy in this setting. Aims: The aim of the current study is to determine iron-prescribing behavior among anemic patients discharged from hospital after GIB. Methods: We performed a retrospective review of 191 patients who were anemic upon discharge after GIB at two quaternary care hospitals in Toronto, Ontario, Canada. Patient comorbidities, medications, endoscopic findings, hemoglobin level, need for transfusion, and iron therapy prescribed in hospital or on discharge were recorded. Descriptive statistics were carried out. Results: The mean hemoglobin (Hgb) level at discharge was 90 g/L (range, 69 to 118 g/L). Only 70 patients (37%) were prescribed iron supplementation therapy upon discharge, most of whom were prescribed oral iron (96%) and few received intravenous iron (4%). Importantly, 31 of the 70 patients prescribed iron on discharge were already taking iron on admission. Iron studies were performed in 25 (13%) patients during admission. Patients who had iron studies performed in hospital were more likely to be prescribed iron at discharge (OR = 2.38). The majority of patients received a red blood cell transfusion in hospital (71%) but this did not affect the likelihood of receiving iron upon discharge. On average, patients with a lower Hgb level at discharge were more likely to be prescribed iron (87 vs. 92, p = 0.004). Conclusions: Patients being discharged with anemia after gastrointestinal bleeding are not routinely being prescribed iron on discharge. Recent evidence suggests benefit from iron replacement therapy in these patients and it is unclear why clinicians aren't prescribing more iron therapy to their patients. Newer clinical guidelines should add recommendations about iron therapy in patients after gastrointestinal bleeding. Educational and quality improvement initiatives may be helpful in encouraging more clinicians to prescribe iron to these patients. Funding Agencies: None